2016
DOI: 10.1088/0957-4484/27/32/324005
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation-induced degradation of PTB7 investigated by valence band and S 2pphotoelectron spectroscopy

Abstract: Monochromatic radiation with known absolute radiant power from an undulator at the electron storage ring Metrology Light Source (MLS) was used to irradiate PTB7 (a thieno[3, 4-b]thiophene-alt-benzodithiophene polymer) thin films at wavelengths (photon energies) of 185 nm (6.70 eV), 220 nm (5.64 eV), 300 nm (4.13 eV), 320 nm (3.88 eV), 356 nm (3.48 eV) and 675 nm (1.84 eV) under ultra-high vacuum conditions for the investigation of radiation-induced degradation effects. The characterization of the thin films is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
(55 reference statements)
1
11
0
Order By: Relevance
“…At longer exposure times, it was shown that the aromatic structure was broken and R'-SOx groups formed. Recently, Darlatt et al studied the stability of PTB7 inside a UHV system with external radiation sources and showed that UV irradiation in vacuum still induces chemical changes [16].…”
Section: Introductionmentioning
confidence: 99%
“…At longer exposure times, it was shown that the aromatic structure was broken and R'-SOx groups formed. Recently, Darlatt et al studied the stability of PTB7 inside a UHV system with external radiation sources and showed that UV irradiation in vacuum still induces chemical changes [16].…”
Section: Introductionmentioning
confidence: 99%
“…Darlatt et al studied by ultraviolet photoelectron spectroscopy (UPS) and S 2p X-ray photoelectron spectroscopy (S 2p XPS) the effect of the irradiation wavelength on the PTB7 stability, in conditions where oxygen and moisture are absent. 17 They concluded that photons of wavelengths > 320 nm provoke no significant degradation (at shorter irradiation wavelength, PTB7 degradation would only concern the S atom of the structure). UPS and XPS are very sensitive methods but, as surface analysis techniques, they probe only the first few nanometres of exposed deposits.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, due to the complexity of the chemical structure of PTB7 (and the same is true for most of the recent push-pull low band-gap copolymers) numerous and sometimes conflicting mechanisms were suggested to account for the PTB7 photochemical reactivity. Darlatt et al 17 and Shah et al 18 have focused on the intrinsic light induced degradation of PTB7 and suggested different processes based on experimental study and Density Functional Theory (DFT) modelling respectively. In the same way, different mechanisms were proposed by Kettle et al 19 Son et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4b shows the high-resolution S 2p peak fitting results of the SSCM surface. The S 2p was deconvoluted into four components: the peaks centered at 162.3 eV and 163.0 eV were respectively assigned to S−C (2p3/2) bonds and S−C (2p1/2), and the components at 163.7 eV and 164.7 eV were attributed to S−Cu (2p3/2) and S−Cu (2p1/2) groups, respectively [47] . Moreover, the high-resolution C 1s peaks of the original CM and SSCM were also fitted, and the results were shown in Figs.…”
Section: Xps Analysismentioning
confidence: 99%